2020
DOI: 10.1002/cctc.202001141
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Heterogeneous Catalysis for Ammonia Synthesis

Abstract: Scheme 1. Electron flow transfer from promoter, support to B 5 active site of Ru and then to π* orbital of N 2 with reduced bond order as seen from the Molecular orbital diagram.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 183 publications
(491 reference statements)
2
88
0
Order By: Relevance
“…[16] Promisingly, recent research on ruthenium-based catalysts addresses these issues by support or promoter changes. [17] Simultaneously, other metals indicated by the volcano curve were tested and proved to show considerable activity when properly prepared and augmented. [5] Cobalt, which at first was used as iron [18,19] or molybdenum dopant in bimetallic catalysts, [20] evolved to standalone active phase.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Promisingly, recent research on ruthenium-based catalysts addresses these issues by support or promoter changes. [17] Simultaneously, other metals indicated by the volcano curve were tested and proved to show considerable activity when properly prepared and augmented. [5] Cobalt, which at first was used as iron [18,19] or molybdenum dopant in bimetallic catalysts, [20] evolved to standalone active phase.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of alternative catalytic materials and systems have been explored for NH 3 synthesis. [8][9][10][11] Lithium (Li), in particular, has been considered to hold the key to NH 3 production at ambient pressure. [6,[12][13][14][15] Li has an extremely low work function and therefore a high reactivity for N 2 activation which is typically the rate-determining step in NH 3 production.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their high activity and long lifespan, Co catalysts are suitable catalyst systems for NH 3 synthesis. 5,6,[20][21][22][23][24] Recently, we revealed that a Bapromoted cobalt catalyst supported on magnesium-lanthanum mixed oxide is an efficient catalyst for ammonia synthesis. 23 The study investigated the kinetics of NH 3 synthesis over the Bapromoted cobalt catalyst and a well-known iron catalyst under various reaction conditions.…”
Section: Introductionmentioning
confidence: 99%